(untitled) (American Journal of Arts and Human Science, 2025)
This study explored the leadership styles and competencies of school heads in the Division of Cagayan de Oro City and their influence on school effectiveness and teacher performance. It aimed to describe the respondents’ profile, assess leadership styles and competencies, and examine their relationship, including variations based on demographic factors. A total of 429 teachers participated, utilizing a modified questionnaire, with data analyzed through descriptive statistics, Pearson correlation, and one-way ANOVA. Results showed that most respondents were female, aged 46 to 55, holding the position of Teacher III, with 25 to 29 years of teaching experience, and pursuing a Master’s degree. Transformational leadership emerged as the most prevalent style, with people management being the strongest competency. A significant correlation was found between transactional leadership and leadership competencies. While teamwork and resource allocation were recognized, there was a need for improved policy enforcement and greater teacher autonomy. The findings emphasized the critical role of leadership styles in school effectiveness and teacher satisfaction. It is recommended that school heads adopt more transformational leadership approaches to foster teacher engagement and independence. Leadership training should focus on contemporary strategies, while teachers should be actively involved in policymaking to enhance implementation. Additionally, recognition systems for outstanding teachers, mentorship programs for novice educators, and continuous evaluations of resource needs should be implemented to strengthen school leadership and instructional quality. These findings underscore the importance of leadership development in enhancing educational outcomes and creating a more effective and motivated teaching workforce.